2016
DOI: 10.1039/c6cs00159a
|View full text |Cite
|
Sign up to set email alerts
|

Icosahedral boron clusters: a perfect tool for the enhancement of polymer features

Abstract: Boron clusters and organic molecules display manifestly different electronic, physical, chemical and geometrical characteristics. These differences highlight the complementarity of organic synthons and boron clusters, and therefore the feasibility of producing hybrid polymers incorporating both types of fragments. This review focuses on the development of hybrid organic-inorganic π conjugated, silane, siloxane and coordination polymers containing icosahedral boron clusters in the last few decades, which have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(84 citation statements)
references
References 56 publications
1
76
0
1
Order By: Relevance
“…HCl solution, and the diethynyl derivatives 2-R were obtained through coupling reaction. The decaborane (14) insertion reaction was carried out to obtain the DCB-R. All compounds were characterized by 1 H, 11 B, and 13 C NMR spectroscopy, elemental analyses and HRMS measurements. The products showed good stability and solubility in common organic solvents such as CHCl 3 , CH 2 Cl 2 , THF, and benzene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HCl solution, and the diethynyl derivatives 2-R were obtained through coupling reaction. The decaborane (14) insertion reaction was carried out to obtain the DCB-R. All compounds were characterized by 1 H, 11 B, and 13 C NMR spectroscopy, elemental analyses and HRMS measurements. The products showed good stability and solubility in common organic solvents such as CHCl 3 , CH 2 Cl 2 , THF, and benzene.…”
Section: Resultsmentioning
confidence: 99%
“…Even though intense luminescence can be observed in the solution state, optical properties were often spoiled through ACQ by intermolecular interactions in the solid state. [5][6][7] It has been reported that some of the o-carborane [8][9][10][11][12][13] derivatives presented AIE [14][15][16][17][18][19][20][21] and can be applied as a solid-state luminescent material. [1][2][3] Intense solid-state luminescent properties originating from AIE were found and applied for developing the conjugated materials, including polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound belongs to a large and rapidly growing family of species that contain an ether ring attached to the boron cage via an oxonium atom [9][10][11][12]. All other members are derived from closo-borate ions such as cobalt bis(dicarbollide) [13,14], decaborate [15,16], dodecaborate [17][18][19], or 1-carba-undecahydroundecaborate [20]; most of which have been used in numerous emerging applications, among others, advanced materials [21,22], organic conducting polymers [23,24], radionuclide partitioning [25,26], biology, and medicine [8,[27][28][29][30][31][32][33][34][35][36][37]. Surprisingly enough, the nidosystem from this family of compounds, namely compound 1, has largely remained outside the stream of main interest, despite its potential for the introduction of open-cage boron polyhedra to functional molecules and materials.…”
Section: Introductionmentioning
confidence: 99%
“…Theu nique o-carborane bears multiple properties including three-dimensional pseudo cage structure and dual electronic effects, [7] and has proven to be ap romising building block for photofunctional materials. [8,9] However, highly efficient white-light emission in the solid state by one single carborane-based organic molecule has not been reported. As an electronic acceptor of the o-carboranyl unit, multiple emissions from both the charge transfer (CT) and locally excited (LE) state might be generated for o-carborane-based luminophores.M oreover,t he o-carborane cage offers functionalizable positions with which both molecular structures and crystal packing structures might be tuned.…”
mentioning
confidence: 99%